2018
DOI: 10.1093/ibd/izy304
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Calprotectin Responses Following Induction Therapy With Vedolizumab in Moderate to Severe Ulcerative Colitis: A Post Hoc Analysis of GEMINI 1

Abstract: BackgroundIn patients with ulcerative colitis (UC), fecal calprotectin (FC) concentrations correlate with endoscopic inflammation evidence. This study investigated the effect of vedolizumab induction on FC concentrations and whether FC concentrations could be a reliable surrogate measure of disease status.MethodsData from the placebo-controlled, phase 3 trial GEMINI 1 were used to evaluate week-6 relationships between outcomes (including clinical remission, mucosal healing [MH], and endoscopic remission) and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 37 publications
0
19
2
1
Order By: Relevance
“…In previous studies, analyzing data from the GEMINI UC registration trial on the ability of FC in combination with clinical data on week 6 to predict endoscopic remission have shown only moderate predictive value 21,22 . A possible explanation for the discrepancy between these findings and the accurate correlation of FC and endoscopy in our study may be that in the VDZ registration trials the evaluation of the response to VDZ induction have been scheduled too early.…”
Section: Discussioncontrasting
confidence: 81%
“…In previous studies, analyzing data from the GEMINI UC registration trial on the ability of FC in combination with clinical data on week 6 to predict endoscopic remission have shown only moderate predictive value 21,22 . A possible explanation for the discrepancy between these findings and the accurate correlation of FC and endoscopy in our study may be that in the VDZ registration trials the evaluation of the response to VDZ induction have been scheduled too early.…”
Section: Discussioncontrasting
confidence: 81%
“… 28 FC data from the GEMINI I trial have shown only a moderate predictive value of FC at week 6 to predict endoscopic remission at week 6. 19 Possible explanations for the discrepancy between these findings and the high diagnostic accuracy of low FC and endoscopic response in our study are not only the earlier timing of the endoscopy in the GEMINI trial but, most importantly, the endpoint of endoscopic remission instead of endoscopic response. Taken together, the GEMINI and our study suggest that a response to VDZ with improvement of mucosal inflammation may be evaluated as early as week 8, whereas the optimal timing to evaluate further improvement towards mucosal healing requires further research.…”
Section: Discussioncontrasting
confidence: 77%
“… 12 , 14 18 To date, the potential of FC to early predict response to VDZ induction therapy is largely unknown as studies have mainly focused on a single FC measurement. 19 To investigate whether early FC level measurements are indicative for mucosal improvement, as observed by endoscopy and histology at week 16, FC levels at predefined time points were assessed after the initiation of VDZ therapy.…”
Section: Introductionmentioning
confidence: 99%
“…39 It has been proposed as a predictive marker of mucosal healing in UC patients treated with anti-TNF, 40 and of clinical remission in patients treated with VDZ. 19 Of note, both clinical trials 41 and real life studies 18 highlighted that VDZ promoted a significant reduction of FC in UC patients. However, the evaluation of FC, as a predictive marker of mucosal healing in VDZ-treated patients, has never been investigated.…”
Section: Discussionmentioning
confidence: 99%